Modeling of Carbonated Metabolites Production by Clostridium butyricum W5 Under Anaerobic Conditions for Optimization of Hydrogen Metabolic Production - Diaz Valencia, Andres Camilo; Garzon Fajardo, Gustavo Adolfo; Sierra Vargas, Fabio E.; Guerrero Fajardo, Carlos A. (Journal of Technology Innovations in Renewable Energy, 2013)
Hydrogen production has been one of the most studied problematics nowadays because of the worldwide needs of change in energy sources for daily use, industrial use and laboratory use. In addition, we can also mention the importance of this energy sources to be clean, self-sustainable and of course profitable for the industry, that is the reason why in this work we studied one of the most common hydrogen-producer microorganisms, Clostridium butyricum. This bacterial specie was chosen because it’s metabolic pathways have been widely studied and it’s an easy-obtainable microorganism present in almost any kind of anaerobic environment such as some zones of soil, human intestines and others, in addition to that, we can also mention some other species for hydrogen production: Kleibsella pneumoniae and Citrobacter freundii which can also be used for the modelation process and the industrial process of production. In this work we developed a process model about the metabolic pathways of C. butyricum in order to understand the hydrogen production process and reveal the points where it can be optimized. Mainly, the model was designed so it could predict the comportment of the process in the exponential phase of growth of the bacteria. Stoichiometric analysis was performed in order to create theoretical curves of the production of hydrogen and other metabolites. Part of the study was performed based in experimental results exposed by other authors, the model was developed in JMCAD ( an open-source software for complex dynamic system modeling based in Java. The predicted results are comparable with the experimental ones as it can be seen in the results section, the R² of all the curves was (near) to 0,97 so we could ensure a close relation with the reality. Some suggestions in order to maintain the exponential phase of growth in the cultures of C. butyricum are exposed and explained further in the article.